2020
DOI: 10.1002/app.50274
|View full text |Cite
|
Sign up to set email alerts
|

Improving the dispersion of MWCNT and MMT in PVDF melts employing controlled extensional flows

Abstract: Poly (vinylidene fluoride) (PVDF) has been widely explored to produce polymer nanocomposites possessing outstanding combinations of properties. In this work, the impact of extensional melt flows on the dispersion, relaxation and crystallinity of PVDF nanocomposites filled with multiwalled carbon nanotubes (MWCNT) and montmorillonites (MMT) was studied. Extrusion was employed to produce nanocomposites containing 3 wt% of fillers, named: (i) PVDF/3 wt% MWCNT, (ii) PVDF/3wt%MMT, and (iii) PVDF/1.5wt%MWCNT/1.5 wt%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In this process, the biocomposite precursors were initially mixed for 5 min and then processed by a mini single screw extruder Filmaq3d STD (Figure 1), operating at 30 rpm screw speed and 170°C, following the previous reports 34 . The biocomposite was extruded through a ring‐shaped matrix, and the obtained filaments were cooled using a water bath system (25°C) and finally collected by a filament winder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the biocomposite precursors were initially mixed for 5 min and then processed by a mini single screw extruder Filmaq3d STD (Figure 1), operating at 30 rpm screw speed and 170°C, following the previous reports 34 . The biocomposite was extruded through a ring‐shaped matrix, and the obtained filaments were cooled using a water bath system (25°C) and finally collected by a filament winder.…”
Section: Methodsmentioning
confidence: 99%
“…Schematic illustration of the single‐screw extruder employed, according to Goes et al 34 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…A few works reported the effect of the elongational flow in inducing morphology evolution in carbon nanotubes (CNTs)-containing nanocomposites [198][199][200][201][202][203]. Generally, the application of the extensional flow during the processing causes the debundling of the CNT clusters formed during the melt mixing step because of attractive inter-tube interactions, resulting in an improvement of the extent of dispersion of the embedded fillers and in the obtainment of more uniform and homogeneous morphologies.…”
Section: Morphology Evolution Of Polymer-based Composites and Nanocomposites Under Elongational Flowmentioning
confidence: 99%
“…[5] In general, it is observed that the rigid additives hinder the movement of polymer molecules leading to an increase in stiffness and strength. [10][11][12][13][14][15] Strength and stiffness also depend on the size, quantity, shape of the additives, and interfacial adhesion. [5] It was observed that beyond a certain volume fraction of the additive, the tensile strength of the composite decreases whereas its elastic modulus increases.…”
Section: Introductionmentioning
confidence: 99%
“…Metal/polymer composites are attractive alternatives that address these concerns. [14,24,25] However, most of these additives fail to increase the strain at failure or ductility in the material and their strength to weight ratio is less compared to CNTs/nanoclay. [14] Nevertheless, some studies have shown that nanoalumina has been able to marginally increase the ductility in the polymer.…”
Section: Introductionmentioning
confidence: 99%